WHAT DEFINES THE EXTENT OF LYMPHODISSECTION FOR EARLY GASTRIC CANCER? - I. N. Turkin; M. I. Davydov (Сибирский онкологический журнал)
Surgery strategy for patients with early gastric cancer remains disputable. The main reason of controversy is the extent of surgical intervention, namely, whether D2 dissection  improves treatment outcomes of early gastric cancer? The present study demonstrates treatment outcomes of 394 patients who underwent surgery for early gastric cancer between 1990–2008. The major risk factors for lymphogenic metastasis (lymphatic invasion, cancer invasion into submucous layer, tumor size > 4.0 cm venous invasion, tumor spread to the esophagus, macroscopic types 0I and 0III and poorly-differentiated tumor) have been found to be an absolute indication for D2 lymphodissection. The restriction of surgery extent to D1-lymphodissection is possible only in patients with negligibly low risk of metastasis regardless of the type of early cancer.